THE USE OF INMATE PLACEMENT SCREENING INSTRUMENTS (ISPN) AT CLASS IIA BEKASI CORRECTIONAL FACILITY - Savira, Muhammad Nuridzati; Rahayu, Mulyani (Universitas Nusa Cendana, 2025)
This study analyzes the implementation of the Inmate Screening Placement Instrument (ISPN) at Bekasi Class IIA Correctional Institution. Using qualitative methods, data were collected through in-depth interviews, observations, and document analysis. The findings highlight that ISPN is a vital tool for assessing inmate risk and determining proper placement based on criteria such as sentence length, remaining sentence, and type of offense. Despite its significant role, challenges such as overcrowding and limited resources hinder its full implementation. Effective communication between officers and inmates positively influences the screening process. However, time constraints often limit the depth of interaction, potentially impacting data accuracy. The study underscores the importance of resource availability, professional officer attitudes, and a well-structured organizational framework in ensuring successful ISPN implementation. Overcrowding and a lack of sufficient staff are major barriers, emphasizing the need for additional training and improved facilities. ISPN positively impacts inmate rehabilitation and security within the institution by minimizing conflicts and enhancing cooperation among inmates. However, consistent evaluation and strategic improvements are essential to optimize its implementation. Addressing existing challenges will enable ISPN to function more effectively as a tool for inmate rehabilitation and reintegration. Keywords: Inmate Screening; Rehabilitation; Correctional Institution